Pendekatan HIRADC untuk Mengidentifikasi Risiko Keselamatan dan Kesehatan Kerja di Perpustakaan Sekolah - Rahmayani, Amalia Azka; Muwahidah, Qanita ‘Abida (Fakultas Teknik UMRI, 2026)
School libraries are often overlooked in terms of structured occupational health and safety (OHS) management, as they are commonly perceived as relatively safe work environments, even though they contain a variety of potential hazards. This study employed a qualitative descriptive approach involving three school libraries in the Special Region of Yogyakarta. Data were collected through observation, measurement, and document review, then analyzed using the HIRADC method. The study identified 11 potential hazards across five factors: physical (3 hazards), chemical (2), biological (2), ergonomic (2), and psychological (2). Risk assessment revealed one high-level hazard (presence of flammable materials, RR=15), four medium-level hazards (RR=6–9), and six low-level hazards (RR=2–4). Administrative controls primarily through SOP development and routine staff training dominated the recommendations, supplemented by engineering controls such as ventilation systems and fire detection installations. These findings underscore the need for a structured OHS program in school libraries to sustainably protect the safety of librarians and library users.